Innovation Leadership in Supply Chain Efficiency: The Role of Process Improvement and Information Technology - Purwoko, Purwoko; Fikri, Muhammad Ali (Journal Corner of Education, Linguistics, and Literature, 2024)
Supply chain management is closely related to the operational processes in an organization. Innovation leadership plays a role in efficiently managing the improvement of supply chain processes and information technology from upstream to downstream. This study analyzes the influence of innovation leadership on supply chain efficiency mediated by process improvement and information technology. This research data was obtained from micro, small and medium enterprises in the creative economy sector in the Special Region of Yogyakarta and obtained as many as 50 respondents. This study uses Smart PLS 4.0 software as a data analysis tool. The results of the study prove that innovation leadership has a positive effect on supply chain efficiency, process improvement mediates the influence of innovation leadership on supply chain efficiency, and information technology mediates the influence of innovation leadership on supply chain efficiency.